Model predictive control based consensus scheme of discrete-time multi-agent systems with communication delay. (4th April 2022) - Song, Guanghao; Liu, Xiaohua; Gao, Rong
In this paper, the state consensus of MPC for discrete-time multi-agent systems with communication delays is considered. When there is delay in the process of information transmission between adjacent agents, the control protocol design method of multi-agent system without delay can not deal with this situation. Therefore, a new control protocol design method is needed. Based on the Pontryagin's maximum principle and mathematical induction, a distributed MPC state consensus protocol is presented. In order to facilitate discussion, a new graph is constructed, and the relationship between the new topology graph and the original topology graph is given through a lemma. By using the error between the agent and the neighbour agent, and constructing the Lyapunov-Krasovskii function, a MPC cost function with terminal constraint which is monotonically decreasing, and the conditions for achieving state consensus of discrete multi-agent system with communication delay are given.